Pegadaian: Mengurai Model Pemasaran Di Media Sosial Dan Akademisi - Daniel Susilo (Journal of Economic, Bussines and Accounting (COSTING), 2023)
State-owned enterprises are company that is expected to best the others as they’re owned by the country and the government whether they are from tech-base industry, finance, internet service, or energy resource. Pegadaian as a company also cannot escape from this as they’re one of the financial pillars for the state and the people. Having history to be freed from Dutch colonization, they become the biggest pawnbroker company serving for the people and the state’s economy, the social media becomes their primary tool to construct their own public image through various contents, one of them is the global agenda of eco-friendly campaign as well as using Gen Z Slangs in their content. However, as advanced and updated they are from the public image, a bias still followed through their academic research records. Through examining this, we will discover their other perspective in the financial marketing.